THE PHENOMENON OF ONE SURO TRADITION IN SURAKARTA PALACE : A COMPREHENSIVE STUDY IN ISLAMIC EDUCATION PERSPECTIVE - Fauziyah Qurrota A'yun Tamami; Devina Putri Faradhiba; Syamsul Hidayat (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2024)
This study examines the phenomenon of the One Suro Tradition in the Surakarta Palace from the perspective of Islamic education, the One Suro Tradition is one of the cultural rituals carried out by the Javanese people, especially in the Surakarta palace environment, which has important meanings both spiritually and culturally. This study uses a qualitative approach with a literature study method, by collecting and analyzing data from various related literature. The results of the study show that the One Suro Tradition contains Islamic educational values such as piety to Allah, solidarity, wisdom, example, respect for ancestors, as well as self-control and patience. These values are taught through various rituals such as fasting, meditation, and heirloom carnivals. This research contributes to a deeper understanding of the integration between Islamic values and local wisdom in the context of Islamic education, as well as its relevance to Indonesian society about the relationship between traditional culture and religion, as well as increasing the appreciation of cultural heritage and religious values in formal and non-formal education.